Analisis Pengaruh Sumber Daya Manusia Strategik Terhadap Kepuasan Kerja dan Kinerja pada Sektor Publik: Studi pada SKPD Kota Banjarmasin - Basuki Basuki; Ervica . Jamilah; Lamsah Lamsah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The most important of the essential functions of human resource management is to take care of skilled employees. The process is normally divided into two categories: first category includes different activities such as having health and safety in working centers, performing healthy and sport programs and some other similar activities to save and improve employees' physical characteristics. The second group includes other important issues normally called benefit packages, which includes good health insurance and retiring plans. Whenever an organization provides good benefit package and supporting programs, there is a better job satisfaction among employee. This study try to find out about, the effects of related services to support employee to reach job satisfaction and employee activities in public sectors called SKPD in Banjarmasin City is used 86 random samples. The results show that employees are relatively satisfied from the benefit package of the SKPD and they were relatively happy on working for such organization.